Effects of compensation, informal organization, and commitment on employee retention and productivity in selected banks Ashanti Region, Ghana: The moderating role of job satisfaction - Panin, Rosina Owusu; Kamil, Naail Mohammed; Musah, Mohammed Borhandden; Zakari, Mariama; Issah, Mohammad (Universitas Airlangga, 2024)
In the new global economy, employee productivity has become a central issue of study. The financial services sector in Ghana has garnered significant attention in recent years. Given the growing inefficiencies in the Ghanaian banking industry, which has resulted in the revocation of operational licenses for some banks, this study aims to examine the impact of compensation, informal organization, and commitment on employee retention and productivity. Additionally, the study seeks to explore the moderating role of job satisfaction in selected private and public banks in the Ashanti region. The study utilized a quantitative research approach, sampling 270 respondents from the selected public and private banks in the Ashanti Region using a simple random sampling technique. For data analysis, the study employed multiple linear regression and utilized the PROCESS MACRO for SPSS version 25. The findings indicate that compensation, commitment, and informal organization exert a positive influence on employee retention, thereby affecting productivity. Furthermore, the study revealed that job satisfaction significantly moderates the relationship between compensation and employee retention, but it does not significantly moderate the relationship between informal organization and employee retention. Similarly, job satisfaction does not significantly moderate the relationship between commitment and employee retention.